2014
DOI: 10.1242/dev.107193
|View full text |Cite
|
Sign up to set email alerts
|

Excessive vascular sprouting underlies cerebral hemorrhage in mice lacking αVβ8-TGFβ signaling in the brain

Abstract: Vascular development of the central nervous system and blood-brain barrier (BBB) induction are closely linked processes. The role of factors that promote endothelial sprouting and vascular leak, such as vascular endothelial growth factor A, are well described, but the factors that suppress angiogenic sprouting and their impact on the BBB are poorly understood. Here, we show that integrin αVβ8 activates angiosuppressive TGFβ gradients in the brain, which inhibit endothelial cell sprouting. Loss of αVβ8 in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 79 publications
(119 reference statements)
8
95
1
Order By: Relevance
“…Our data support the idea that there are distinct tissue and temporal context-dependent requirements for specific integrin heterodimers in vascular development (11). Indeed, the only other well-defined example of a non-cell-autonomous role played by integrins in vascular development involves integrin αvβ8 in the CNS and retina, where failure to activate latent ECM-bound TGF-β was an underlying cause of the observed vascular defects (35,36). Interestingly, the palate defect in the Pitx1-cre; Itgb1 f/f embryos phenocopies double-knockouts of integrin β6/β8 and single-knockouts of TGF-β3, suggesting integrin β1-dependent TGF-β signaling in the palate (37,38).…”
Section: Discussionsupporting
confidence: 83%
“…Our data support the idea that there are distinct tissue and temporal context-dependent requirements for specific integrin heterodimers in vascular development (11). Indeed, the only other well-defined example of a non-cell-autonomous role played by integrins in vascular development involves integrin αvβ8 in the CNS and retina, where failure to activate latent ECM-bound TGF-β was an underlying cause of the observed vascular defects (35,36). Interestingly, the palate defect in the Pitx1-cre; Itgb1 f/f embryos phenocopies double-knockouts of integrin β6/β8 and single-knockouts of TGF-β3, suggesting integrin β1-dependent TGF-β signaling in the palate (37,38).…”
Section: Discussionsupporting
confidence: 83%
“…Cerebral angiogenic growth and barriergenesis are modulated by neuroepithelial cues that activate endothelial signaling cascades (Hagan and Ben-Zvi, 2014). These include canonical Wnt or Wnt/β-catenin signaling, which promotes both aspects of vascular development specifically in the central nervous system (CNS), and global regulators of angiogenic growth that have positive (VEGF and SDF1) or negative (Notch and TGF-β) roles (Arnold et al, 2014;Bussmann et al, 2011;Fujita et al, 2011;Gridley, 2010;Larrivee et al, 2012;Mackenzie and Ruhrberg, 2012;Masckauchan and Kitajewski, 2006;Reis and Liebner, 2013). Reck (reversion-inducing cysteine-rich protein with Kazal motifs) is a dimeric multi-domain glycosylphosphatidylinositol (GPI)-anchored protein isolated as a tumor suppressor whose overexpression normalizes the aberrant morphology of transformed fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, when mice with a TGF-␤1 gene knock-in mutation that causes an RGE substitution of the RGD motif are crossed with TGF-␤3-deficient mice they die as a result of severe brain hemorrhage (51), recapitulating the phenotype of integrin ␤8-deficent mice. Given the similarities in phenotypes between ␣v␤8 integrin-deficient mice and TGF-␤1(RGE)/TGF-␤3 double mutant mice, ␣v␤8 integrin has been proposed to act as an "angiogenic switch" in the brain through TGF-␤ activation (52,53). Consistent with the role of ␣v␤8 integrin in TGF-␤1 activation, Yamazaki et al (54) reported that ␤8 integrin was specifically expressed by Schwann cells and involved in latent TGF-␤ activation in the bone marrow, thereby regulating hematopoietic stem cell hibernation.…”
Section: Discussionmentioning
confidence: 99%